Effects of autophagy inhibition on Newcastle disease virus-induced oncolysis in breast cancer cells - Rozilah, Megat Mohamad Irfan (2022)
Researchers have been developing oncolytic viruses (OVs) as an alternative treatment to treat advanced cancer and to combat against the cancer cell resistance towards chemotherapy and radiotherapy. Newcastle disease virus (NDV) is an avian virus which selectively replicates in mammalian cancer cells due to the lack of antiviral immune response in these cells, thus making NDV a good candidate for oncolytic virotherapy. Recently, scientists have explored a novel strategy to fight cancer that is by inhibiting autophagy. Autophagy is a highly conserved cellular degradation mechanism which recycles unused cytoplasmic constituent into new nutrients. Importantly, studies have demonstrated that inhibition of autophagy enhanced NDV-induced oncolysis in several human cancer cells including gastric carcinoma, lung, and glioma cancer cells. Even though studies have been done to show NDV oncolytic effect in breast cancer cells, the effect of autophagy inhibition on NDV-induced oncolysis in breast cancer cells remains unknown. The main aim of this study was to examine the effect of autophagy inhibition on NDV-induced oncolysis in human breast cancer cells MCF7. Two approaches were utilised to inhibit autophagy which were pharmacological inhibitors and short-interfering RNA (siRNA)- mediated protein knockdown. Briefly, MCF7 cells were infected with the recombinant NDV strain AF2240 with GFP (rAF-GFP) with or without autophagy inhibition by the pharmacological autophagy inhibitors, SAR405 and chloroquine (CQ); or by siRNA-mediated knockdown of the autophagy protein Beclin-1 (BECN1). Autophagic activity was observed and quantified using fluorescence microscopy and fluorometer, respectively. MTT assay was used to measure cell death and viral replication was quantified using fluorometer. The results showed that NDV induced autophagy in MCF7 cells at 2 hours post-infection (hpi). Importantly, both autophagy inhibitors, SAR405 and CQ, had no significant effect on NDV-induced oncolysis in MCF7 breast cancer cells, as measured at 24, 48 and 72 hpi. Furthermore, in contrast to our hypothesis, siRNA knockdown of BECN1 significantly reduced the cell death of NDV-infected MCF7 cells at 24 hpi by ~10%, but not at 48 and 72 hpi. Further experiment suggests that this could be due to the reduction of viral replication by more than 50% following treatment with BECN1-targeting siRNA at 24 hpi. In conclusion, NDV induces autophagy in breast cancer cells. Importantly, inhibition of autophagy does not enhance the oncolytic efficacy of NDV in breast cancer cells, instead it reduces the cell death, possibly by suppressing viral replication. Further work can be done to determine if induction of autophagy can enhance the oncolytic efficacy of NDV in breast cancer cells.